The Influence of Sustainability Report, ISO 9001 Certification, and Food Safety Management System Certification toward The Customer Satisfaction in PT XYZ, Sidoarjo - Yuli Kurniawati (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: As the world goes into unpredictable situation, business activities have turned differently. Since the age of corporate social responsibility, sustainability is introduced. To deep dive into human development and social impact, global standards are also required to comply with. This fact is no surprise as business operations affect many aspects in life. This study focuses on the observation of three independent variables; sustainability report, ISO 9001 certification, FSMS (FSSC 22000) certification, and also how they influence customer satisfaction in the industry. Design/methodology/approach: Method used here is a quantitative approach that include classical assumption, multiple linear regression, and also hypothesis tests. Author examines them in an order, to keep the presentation well-structured that is segregated in a few chapters. Findings: Result of the study shows that all of the independent variables influence the dependent variable both partially and simultaneously with R2 score is at 0.42 and its intercept scored at 27.97. Research limitations/implications: This paper is limited to the context of management systems only observing the influence of the three independent variables and one dependent variable as stated in the abstract. Practical implications: This study will support the understanding on how the report of sustainability and management systems to be able to influence the customer satisfaction in business. This may broaden the view on corporate image and improve its acceptance in the society. Originality/value: This paper is originally written by the author with no participation of other researcher/s and only use some journals & books as reference. Paper type: Research paper